2022
DOI: 10.1080/07853890.2022.2124445
|View full text |Cite
|
Sign up to set email alerts
|

An open-label non-inferiority randomized trail comparing the effectiveness and safety of ultrasound-guided selective cervical nerve root block and fluoroscopy-guided cervical transforaminal epidural block for cervical radiculopathy

Abstract: Object To compare therapeutic efficacy and safety of ultrasound (US)-guided selective nerve root block (SNRB) and fluoroscopy (FL)-guided transforaminal epidural steroid injection (TFESI) for cervical spine radiculopathy (CSR). Method 156 patients with CSR randomly received US-guided SNRB verified by FL or FL-guided TFESI. We hypothesised that the accuracy rate of contrast dispersion into epidural or intervertebral foraminal space in the US group was not inferior to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Various studies have shown that there is no significant difference in the success rate, pain relief, and functional improvement between ultrasound-guided SNRB versus fluoroscopy-guided transforaminal injection when treating CSR. However, ultrasound-guided SNRB has the advantage of no radiation, no serious complications, and being more efficient [ 8 , 24 , 28 ]. Some blood vessels are also present around some cervical nerve roots, with the Doppler mode of ultrasound being able to detect any located around the target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that there is no significant difference in the success rate, pain relief, and functional improvement between ultrasound-guided SNRB versus fluoroscopy-guided transforaminal injection when treating CSR. However, ultrasound-guided SNRB has the advantage of no radiation, no serious complications, and being more efficient [ 8 , 24 , 28 ]. Some blood vessels are also present around some cervical nerve roots, with the Doppler mode of ultrasound being able to detect any located around the target.…”
Section: Discussionmentioning
confidence: 99%
“…Some blood vessels are also present around some cervical nerve roots, with the Doppler mode of ultrasound being able to detect any located around the target. This procedure effectively avoids intravascular injection, and enhances the safety of the entire treatment process [ 24 , 28 , 29 ]. In our study, three subjects in the two groups interrupted treatment after vasovagal reaction occurred (adverse reaction rate: 1.87%).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound guidance produces similar clinical response to fluoroscopy-guided interventions but is able to identify arteries in association with the foramen which are subject to inadvertent intravascular injection. 19,20…”
Section: Cervical Radiculopathymentioning
confidence: 99%
“…While ultrasound is not routinely used in the diagnosis of cervical radiculopathy, there is a body of literature demonstrating the utility of ultrasound to guide peri‐radicular injections. Ultrasound guidance produces similar clinical response to fluoroscopy‐guided interventions but is able to identify arteries in association with the foramen which are subject to inadvertent intravascular injection 19,20 …”
Section: Radiculopathymentioning
confidence: 99%
“…Facet joint injections are one of the most common procedures performed by pain management anesthesiologists [5]. Injections can be directed by fluoroscopy, computed tomography (CT), and palpation or loss-of-resistance techniques [6]. Techniques such as fluoroscopy and CT have significant disadvantages.…”
Section: Introductionmentioning
confidence: 99%